Sistema de control y monitoreo de consumo energético para equipos de climatización orientado a internet de las cosas (IOT) (2019)
HVAC systems (Heating, Ventilating and Air Conditioning) consume 40% of total domestic energy, with more than 25% of energy demand in homes and offices in Colombia. According to what has been studied in the state of the art, there are various factors that influence the efficiency of these systems. Some of the factors that influence the behavior of air conditioning systems are: the efficiency inherent to the manufactured system (intrinsic characteristics), the environmental conditions of each region (extrinsic conditions, such as external temperature), the responsible use by the end users, and the perception of comfort on the part of the occupants of the enclosure where the system operates, among others. This research addresses the problem of energy consumption of HVAC systems, from the view of rational consumption based on their operating conditions. The above implies to analyze and correlate the behavior of HVAC systems with changes in the behavior of environmental (external) temperature conditions. In addition, integrate control and monitoring solutions to the Internet of Things (IoT) technologies to manage valuable information based on real time data analysis. Thus, this document summarizes the development of a control system and monitoring of energy consumption for an air conditioning (AC) system oriented to IoT. With the implementation of IoT-based technologies, a significant contribution is made to the monitoring tools, data acquisition and therefore, monitoring for the evaluation of the control techniques of these systems. The monitoring action generates large amounts of data that may be of interest to users, researchers or distribution and marketing companies of air conditioning systems. The document defines the requirements and control techniques for the development of an embedded device using an architecture based on the MQTT protocol applied to the air conditioning system. As well as the stages considered during the implementation in a conventional mini-split HVAC system are described. Finally, the results of the control and monitoring system are compared with the data of the same system without the embedded device in order to validate operation, implementation and integration ith the system